Proses Seeding Dan Aklimatisasi Untuk Pengolahan Anaerob Limbah Cair Produksi Minyak Sawit - Syahrin, Alfi; Andrio, David; Veronika, Nina (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Palm Oil Mill Effluent (POME) was high strength organic wastewater contained COD 40.000 – 60.000 mg/l. To decreased lag phase on anaerobic treatment for treat it, the anaerobic mixed culture bacteria should be acclimatized toward POME. The bioreactor acclimatization process used circulating batch reaktor with worked volume 24 L and ratio wastewater to biomass bacteria was 80:20 (% V/V). The parameter observed in this research was COD and VSS. Seeding process was doing in 7 days with highest efficient of the reduction COD was 34,54% and enhancement VSS 51,71%. Acclimatization process was doing in 10 days with highest efficient of the reduction COD 55,90% and enhancement VSS 19,70%.Keywords : Acclimatization, biomass, bioreactor, circulating batch reactor, COD, lag phase, mixed culture, POME, seeding, VSS,